2014
DOI: 10.1190/int-2013-0199.1
|View full text |Cite
|
Sign up to set email alerts
|

Visual saliency and potential field data enhancements: Where is your attention drawn?

Abstract: Interpretation of gravity and magnetic data for exploration applications may be based on pattern recognition in which geophysical signatures of geologic features associated with localized characteristics are sought within data. A crucial control on what comprises noticeable and comparable characteristics in a data set is how images displaying those data are enhanced. Interpreters are provided with various image enhancement and display tools to assist their interpretation, although the effectiveness of these to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Using visual saliency, we can accomplish this task and make interpreters job relatively easy. Sivarajah et al [15] studied var- ious saliency detection algorithms and observed which one closely mimics the interpreters visual attention when interpreting the gravity and magnetic data for exploration applications. The study concludes that saliency maps can be used to develop new techniques to compensate or augment biases and guide the interpreter's attention to important areas in images.…”
Section: Introductionmentioning
confidence: 99%
“…Using visual saliency, we can accomplish this task and make interpreters job relatively easy. Sivarajah et al [15] studied var- ious saliency detection algorithms and observed which one closely mimics the interpreters visual attention when interpreting the gravity and magnetic data for exploration applications. The study concludes that saliency maps can be used to develop new techniques to compensate or augment biases and guide the interpreter's attention to important areas in images.…”
Section: Introductionmentioning
confidence: 99%